SARC residence - Parra Cancino, Juan; SARC residence Sonic Arts Research Centre, Queen's University Belfast, Northern Ireland February 12-16, 2024 (2024)
guitar, electronics
Lecture, workshop, and Performance of MTT
FRIS
Editorial review
Keywords: Music, Thought and Technology